A novel engineered dermis for in vitro photodamage research. (8th February 2016) - Imparato, G.; Casale, C.; Scamardella, S.; Urciuolo, F.; Bimonte, M.; Apone, F.; Colucci, G.; Netti, P. A.
Abstract: The realization of biologically relevant human tissue equivalents as an in vitro model to investigate human diseases, as well as to test the efficacy or toxicity of novel compounds, is emerging as a new challenge in tissue engineering. Currently, the in vitro three‐dimensional (3D) dermis model mainly involves the use of cells embedded in exogenous non‐human matrices. However, such models feature biological and functional disparities with native dermis, therefore limiting their relevance to the in vivo situation. The purpose of this study was to provide a reliable endogenous human dermal equivalent (HDE) able to recapitulate the extracellular matrix (ECM) remodelling of the native dermis occurring after external damage. To this end, UVA irradiation was used to induce photodamage to both the HDE and to a fibroblast‐populated collagen matrix. The photodamage was investigated at the cellular and ECM level and the results showed that, although a cellular response was detected in both systems, no ECM reorganization characteristic of the in vivo photo‐aged dermis could be detected in the fibroblast‐populated collagen matrix. In contrast in the HDE, the neosynthesized ECM recapitulated the characteristic ageing behaviour of the dermis found in vivo, in terms of collagen and hyaluronic acid synthesis as well as collagen organization remodelling. This study therefore demonstrates the role of the endogenous ECM in recapitulating in vitro the functionality of the human dermis and the proposed HDE as a novel tool for photoprotection trials. Copyright © 2016 John Wiley & Sons, Ltd.